PM3 Study of the Electronic Structure of Coumarins - Tandon, Asha (Asian Journal of Chemistry, 2010)
The coumarins are a family of molecules that have been studied extensively because of their application as laser dyes and their substantial statedependent variation in static dipole moment. In view of this, Parametric Method 3 (PM3) semi-empirical molecular orbital calculations are perfmned on the substituted coumarins for their geometry and electronic properties. It can be seen that our calculated results are in good agreement with available experimental and theoretical estimates.